Changes of a frailty index based on common blood and urine tests during a hospital stay on geriatric wards predict 6-month and 1-year mortality in older people - Jäger J (Clinical Interventions in Aging, 2019)
Jakob Jäger,1,2 Cornel Christian Sieber,1,3 Karl-Günter Gaßmann,1,2 Martin Ritt1,2 1Institute for Biomedicine of Ageing (IBA), Friedrich-Alexander-Universität Erlangen-Nürnberg (FAU), D-90408 Nürnberg, Germany; 2Department of Internal Medicine III (Medicine of Ageing), Geriatrics Center Erlangen, Malteser Hospital Erlangen, D-91054 Erlangen, Germany; 3Department of General Internal Medicine and Geriatrics, Hospital of the Order of St John of God, D-93049 Regensburg, Germany Background: We aimed to evaluate the abilities of a 21-item frailty index based on laboratory blood and urine tests (FI-Lab21) assessed at different points in time, ie, at admission to hospital (FI-Lab21admission) and before discharge from hospital (FI-Lab21discharge), and the change of the FI-Lab21 during the hospital stay to predict 6-month and 1-year mortality in hospitalized geriatric patients. Methods: Five hundred hospitalized geriatric patients aged ≥65 years were included in this analysis. Follow-up data were acquired after a period of 6 months and 1 year. Results: The FI-Lab21admission and FI-Lab21discharge scores were 0.33±0.15 and 0.31±0.14, respectively (P<0.001). The FI-Lab21admission and FI-Lab21discharge both predicted 6-month and 1-year mortality (areas under the receiver operating characteristic curves: 0.72, 0.72, 0.77, and 0.75, respectively, all P<0.001). The predictive abilities for 6-month and 1-year mortality of the FI-Lab21admission were inferior compared with those of the FI-Lab21discharge (all P<0.05). Patients with a reduction in or stable FI-Lab21 score during the hospital stay revealed lower 6-month and 1-year mortality rates compared with the persons whose FI-Lab21 score increased during the hospital stay (all P<0.05). After adjustment for age, sex, and FI-Lab21admission, each 1% decrease in the FI-Lab21 during the hospital stay was associated with a decrease in 6-month and 1-year mortality of 5.9% and 5.3% (both P<0.001), respectively. Conclusion: The FI-Lab21 assessed at admission or discharge and the changes of the FI-Lab21 during the hospital stay emerged as interesting and feasible approaches to stratify mortality risk in hospitalized geriatric patients. Keywords: geriatric wards, frailty, frailty index, cumulative deficit, older people